2016
DOI: 10.1007/s10695-016-0260-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oxidative stress markers in the heart and liver of rainbow trout (Oncorhynchus mykiss walbaum) exposed to the formalin

Abstract: The aim of this study was to examine change in lipid and protein oxidation biomarkers, transamination enzymes and lactate dehydrogenase activities, lactate and pyruvate levels in liver and heart tissue of rainbow trout (Oncorhynchus mykiss Walbaum) that was exposed to formalin baths. Increase of 2-thiobarbituric acid reactive substances and carbonyl derivatives of protein oxidative destruction was noticed only in cardiac tissue of formalin-exposed fish. Activity of lactate dehydrogenase and lactate level in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 54 publications
(100 reference statements)
0
11
0
Order By: Relevance
“…In the same tissues of O. mykiss exposed for 24 h to 50–200 mg/L of formalin, there was an increase in malondialdehyde activity and a decrease in glutathione, catalase, glutathione and peroxidase activities (İspir et al, 2017). Exposure of O. mykiss to 200 ml/m 3 of formalin resulted in metabolic plasticity in the liver with decreased levels of oxidative stress biomarkers and aminotransferases activity (Tkachenko & Grudniewska, 2016). On the other hand, Smith et al (1987) reported that Oncorhynchust shawytscha exposed to 618.0 mg/L of formalin showed no consistent effect on gill Na + , K + ‐ATPase activity.…”
Section: Histomorphological Alterations On Gills and Haematopoietic Omentioning
confidence: 99%
“…In the same tissues of O. mykiss exposed for 24 h to 50–200 mg/L of formalin, there was an increase in malondialdehyde activity and a decrease in glutathione, catalase, glutathione and peroxidase activities (İspir et al, 2017). Exposure of O. mykiss to 200 ml/m 3 of formalin resulted in metabolic plasticity in the liver with decreased levels of oxidative stress biomarkers and aminotransferases activity (Tkachenko & Grudniewska, 2016). On the other hand, Smith et al (1987) reported that Oncorhynchust shawytscha exposed to 618.0 mg/L of formalin showed no consistent effect on gill Na + , K + ‐ATPase activity.…”
Section: Histomorphological Alterations On Gills and Haematopoietic Omentioning
confidence: 99%
“…Furthermore, the levels of urea were not dangerous and the inclusion of DLP in the fish diet, at the level tested in the present study, did not affect the general metabolism of gilthead seabream. This crucial aspect was also confirmed from the trend of ALT and AST, which provide information of liver welfare status, protein metabolism and energy management (Bulfon et al, ; Ismail & Mahboub, ; Shirdel et al, ) and are also indicators of stress (Ismail & Mahboub, ; Shirdel et al, ; Tkachenko & Grudniewska, ). High values of ALT and AST for prolonged time are related with hepatic damage or a disturbance in the Krebs cycle, and may indicate cellular necrosis (Ismail & Mahboub, ).…”
Section: Discussionmentioning
confidence: 79%
“…In these situations, there is a release of glucose through glycogenolysis (Laiz‐Carrión et al, ; Soengas & Aldegunde, ), lipolysis (Shirdel, Kalbassi, Shokri, Olyaei, & Sharifpour, ) and the activation of gluconeogenesis (Laiz‐Carrión et al, ; Shirdel et al, ) and fish use less exogenous glucose. Lactate levels also increase due to glucose reset lactate by gluconeogenesis (Tkachenko & Grudniewska, ). In our study, we confirm the hypoglycaemic activity of citrus peels suggested in previous studies (Menichini et al, ; Padilla‐Camberos et al, ), since gilthead seabream fed for 15 days with DLP showed decreased glucose and lactate levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed higher hepatic MDA levels in Mytilus galloprovincialis exposed for 10 days to 1 mg/L quaternium-15, a strong formaldehyde releaser preservative (Faggio et al, 2016;Pagano et al, 2016), and elevated ROS and MDA production in mouse liver treated with formaldehyde (Liu et al, 2014a, Ye et al, 2013. Moreover, levels of thiobarbituric acid reactive substances (TBARS) generated during oxidative stress were increased after a formalin bath at 0.2 mL/L for 20 min in rainbow trout O. mykiss (Tkachenko and Grudniewska, 2016). The results we obtained in the digestive gland of S. woodiana were similar to those reported above, suggesting a strong correlation between lipid peroxidation and the formaldehyde by-products.…”
Section: Discussionmentioning
confidence: 97%